The Effect of Local Taxes, Human Development Index, And Investment on Labor Absorption on Economic Growth - Satoto, Eko Budi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
The study seeks to examine how local taxes, the human development index, and investments in labor absorption affect economic growth. Utilizing Smart PLS 3.0 for testing and statistical analysis, the research approaches include SEM analysis tools. The study’s findings demonstrate that a variety of elements, including regional taxes, the Community Development Index, and investments, have a favorable and considerable impact on the region’s ability to absorb workers. This demonstrates how raising local tax income, raising the community development index, and raising investment may all contribute to more job prospects in the area. The research also demonstrates that the same elements—local taxes, the Community Development Index, and investments—have a favorable and considerable influence on regional economic growth. This suggests that more investment, improved community development, and higher local tax revenues can all have a favorable impact on the area’s economic growth. Last but not least. Furthermore, this study shows that employment has a positive and substantial impact on economic growth, indicating that a rise in the employment rate might help the region’s economy expand as a whole.